THE INDEXING CONTEXT FOR CATALOGING BOOKS USING (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
We evaluated study of the indexing process in the cataloging at university libraries, using a socio-cognitive approach to analyze procedures, difficulties and perceptions of librarians, users, and managers. The methodology consisted of the Individual and Group Verbal Protocols applied in university libraries. The results were the absence of procedures for book subject analysis and representation, incompatibility of indexing language, and problems of subject retrieval from the catalog. We have concluded that is tendency of catalogs to act as databases. Therefore, the cataloguer should present a posture of commitment similar to that of an indexer who works in the production of these bases.link para o texto completo: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/485/769